Managing Cancer And Living Meaningfully (CALM): randomised feasibility trial in patients with advanced cancer. Issue 2 (19th January 2016) - Lo, Chris; Hales, Sarah; Chiu, Aubrey; Panday, Tania; Malfitano, Carmine; Jung, Judy; Rydall, Anne; Li, Madeline; Nissim, Rinat; Zimmermann, Camilla; Rodin, Gary
Abstract : Background: Managing Cancer And Living Meaningfully (CALM) is a brief individual psychotherapy for patients with advanced cancer. In an intervention-only phase 2a trial, CALM showed promising results, leading to the present 2b pilot, which introduces procedures for randomisation and improved rigour in preparation for a phase 3 randomised controlled trial (RCT). Aims: To test trial methodology and assess feasibility of a confirmatory RCT. Design: A parallel-arm RCT (intervention vs usual care) with 3 and 6-month follow-ups. Assessment of feasibility included rates of consent, randomisation, attrition, intervention non-compliance and usual care contamination. Primary outcome: depressive symptoms (Patient Health Questionnaire-9; PHQ-9). Secondary outcomes: major depressive disorder (MDD), generalised anxiety, death anxiety, spiritual well-being, attachment anxiety and avoidance, self-esteem, experiential avoidance, quality of life and post-traumatic growth. Bayesian conjugate analysis was used in this low-powered setting. Setting/participants: 60 adult patients with advanced cancer from the Princess Margaret Cancer Centre. Results: Rate of consent was 32%, randomisation 78%, attrition 25%, non-compliance 37% and contamination 17%. There was support for potential treatment effects on: PHQ-9, OR=1.48, 95% Credible Interval (CRI.95 ) (0.65, 3.38); MDD, OR=1.56, CRI.95 (0.50, 4.84); attachment anxiety, OR=1.72, CRI.95 (0.73, 4.03); and attachment avoidance, OR=1.58, CRI.95 (0.67, 3.71). There was no support for effects on the seven remaining secondary outcomes. Conclusions: A phase 3 CALM RCT is feasible and should aim to detect effect sizes of d=0.40, with greater attention to issues of compliance and contamination. Trial registration number: NCT02353546.